The dynamic evolution of the de Winter ECG pattern that is easily overlooked and life-threatening: a case report and literature review - Chen, Yingmei; Chen, Bao; Zhang, Lili; Liao, Wang; Wang, Miao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRapid diagnosis of patients with acute coronary syndrome (ACS) is crucial for saving their lives. The de Winter electrocardiogram (ECG) pattern is rare and is treated similarly to ST-segment elevation myocardial infarction (STEMI) and acute thrombotic occlusion of the coronary artery. The de Winter ECG pattern has been previously reported, but its dynamic evolution and characteristics have not been summarized.MethodsWe reported two male patients who presented with de Winter ECG pattern at rest, and neither patient had a family history of hypertension, diabetes, or coronary heart disease. An urgent examination in our hospital showed elevated levels of cardiac troponin T. Both patients underwent emergency coronary angiography, which revealed subtotal proximal left anterior descending (LAD) stenosis. There was an improvement in chest tightness and pain after stent implantation. Serial ECGs before and after percutaneous coronary intervention showed dynamic evolution of ECG. A literature review was conducted to examine reported coronary angiography findings in patients with the de Winter pattern. The review focused on the dynamic evolution of the ECG and the accuracy of this pattern in diagnosing acute coronary artery occlusion (culprit vessel). It also highlighted the danger of the de Winter ECG pattern and the importance of emergency treatment.ResultsEighteen patients, including two of our patients, presented with the de Winter ECG pattern. Our two cases demonstrated two different forms of ST-segment dynamic evolution, with Case 2 being the only one among 18 cases that dynamically evolved into a life-threatening non-STEMI (NSTEMI). All cases were male patients with sudden chest pain. ECG examination showed an upward-sloping ST-segment depression with tall symmetrical T waves in the chest leads, and multiple follow-up ECGs revealed dynamic ST-segment evolution. Emergency coronary angiography showed occlusion of the LAD, left main artery (LMA), right coronary artery (RCA), first diagonal branch (D1), and left circumflex (LCX) artery as well as multiple vascular lesions. Most cases support subtotal stenosis or complete occlusion of the anterior descending artery. Timely identification of the de Winter ECG pattern and prompt transfer to the catheterization laboratory for emergency revascularization can be lifesaving and improve prognosis.ConclusionThese two cases and the literature review indicated that the de Winter ECG pattern is dynamically evolving. Its ECG pattern evolution is variable, progressing to STEMI, NSTEMI, Wellens, or even a normal. In patients presenting with chest pain, a de Winter ECG pattern, regardless of the subsequent dynamic evolution of the ECG, indicates the presence of severe coronary artery stenosis. The de Winter ECG pattern may be an early manifestation of ACS and requires urgent coronary angiography to save the patient's life and improve prognosis.